Gestão do conhecimento tácito: um estudo de caso em uma organização pública de pesquisa e ensino em Minas Gerais - Mauro Araujo Camara (2017)
This thesis aimed at investigating the importance of expertise in the context of a research and education public organization. Due to the lack of deepened studies on tacit knowledge when it comes to Knowledge Management in the field of Information Science, a study was proposed to fill this gap. The literature of the area illuminates the initiatives that make knowledge structured, explicit, transformed into some object or device, turning itself into or becoming a reified knowledge management. Knowledge Management can go further, especially when it is intended to preserve the expertise developed in some form of life by workers. Using the fundamentals of the tacit knowledge management and the elements that emerge in its surroundings as perception, judgment and immersion, this research sought to identify the existence of tacit abilities in a structured task. The study was developed in a public organization of research and education of Minas Gerais. The empirical part was done through the analysis of 96 questionnaires answered by servants and 08 in-depth interviews with regional accounts group servers as well as the analysis of the task of calculating the quarterly GDP of the state of Minas Gerais, trying to answer the question: why cannot this task be done by just using computers? Considering that this is a qualitative exploratory research, the Grounded Theory methodology and the theoretical object of the Course of Action were used. The technique adopted was the analysis of the activity of the employees proceedings in action, which consists of monitoring, observing and conducting recursive self-confrontation interviews. By this technique it was possible to identify tacit abilities that interfere in the accomplishment of the task. With the results achieved, it was concluded that, besides not being possible to perform the task totally in an automated way, it is feasible to bring the tacit abilities the executors possess to their consciousness so that these can be preserved in the organization through focused learning. It was also concluded that it is feasible to implement the tacit knowledge management in a public organization of research and education so as to develop such skills by less experienced servers, opening a vast field to be explored by Information Science